2012
DOI: 10.1002/asia.201200674
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Studies of the Asymmetric Binary‐Acid‐Catalyzed tert‐Aminocyclization Reaction: Origins of the CH Activation and Stereoselectivity

Abstract: A mechanistic study of the tert-aminocyclization reaction was performed by using DFT calculations and labeling experiments. The results showed that the reaction proceeded through a rate-limiting-, stereospecific-, and suprafacial 1,5-H-transfer pathway, followed by a barrier-less C-C bond formation. The mode of stereocontrol for facial selection could be ruled out owing to the high activation energy of C-N bond rotation. The intrinsic feature of this Lewis acid activation was found to be the activation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(17 citation statements)
references
References 60 publications
1
16
0
Order By: Relevance
“…In this case, chiral phosphoric acid 71 is used as a ligand which enhances the electrophilicity of the magnesium center. A related theoretical study37 suggested that the stereoselectivity observed stems from the hydride transfer step, consistently with the proposals of Akiyama and Reinhoudt 35a. 6b…”
Section: Enantioselective 15‐hydride‐shift Processessupporting
confidence: 77%
“…In this case, chiral phosphoric acid 71 is used as a ligand which enhances the electrophilicity of the magnesium center. A related theoretical study37 suggested that the stereoselectivity observed stems from the hydride transfer step, consistently with the proposals of Akiyama and Reinhoudt 35a. 6b…”
Section: Enantioselective 15‐hydride‐shift Processessupporting
confidence: 77%
“…(Table 1, entry 5), whereas the others were found to be ineffective Lewis acid mediators for the transformation. Other lanthanide metal salts could furnish the product in a range of yields and enantioselectivities, all of which were inferior to that obtained with scandium(III) triflate ( Table 1, entries [6][7][8][9]. The structure of the N,N'dioxide ligands had a large effect on the enantioselectivity.…”
Section: Resultsmentioning
confidence: 96%
“…Since Reinhoudt et al [2] provided an alternative method of cleavage of a C(sp 3 )ÀH bond through an intramolecular tandem 1,5-hydride shift/ring closure process in 1984, variants of this rearrangement have been reported. [3][4][5][6] One challenge associated with this chemistry has been to render it enantioselective under mild reaction conditions. Chiral organocatalysts (e.g., chiral phosphoric acid and iminium) and chiral Lewis acids (e.g., Mg II , Co II and Au I coordinating with chiral ligands) are general catalysts that are used for the asymmetric transitions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a mechanism is also known for alkyllithium compounds that contain a β‐hydrogen atom, and hence act as hydride donors 15. Conceptually related [1,5]‐hydride‐transfer reactions, from carbon atoms α to the nitrogen atom to an electron acceptor, such as an activated vinyl group,9d,f,k,l iminium bond,9e imine,9c,h,i or aldehyde9j have been reported in the literature.…”
Section: Resultsmentioning
confidence: 99%